Microsurgical Approach for True Posterior Communicating Artery Aneurysms: Literature Review and Illustrative Case - Masuoka, Jun; Yoshioka, Fumitaka; Furukawa, Takashi; Koguchi, Motofumi; Ito, Hiroshi; Inoue, Kohei; Ogata, Atsushi; Nakahara, Yukiko; Abe, Tatsuya (Asian Journal of Neurosurgery, 2022)
True posterior communicating artery (PCoA) aneurysms are rare. Although true PCoA aneurysms have been reported to be located close to the internal carotid artery, at the middle part of PCoA, or close to the posterior cerebral artery; the best surgical approach to treat true PCoA aneurysms in each location remains unclear. We conducted a literature review using data from PubMed. Data on demographics, location, and projecting direction of the aneurysm, surgical approach, and surgical complications were collected. A total of 47 true PCoA aneurysms were included. Twenty-nine aneurysms originated from the proximal portion, 10 from the middle portion, and 6 from the distal portion; there were two giant aneurysms. The ipsilateral pterional approach was used for 37 true PCoA aneurysms (27 in proximal portion, 8 in middle portion, and 2 in distal portion of PCoA). The anterior temporal approach was used for two distal-portion aneurysms and one giant aneurysm. The anterior subtemporal approach was used for one distal-portion aneurysm. The subtemporal approach was used for two middle-portion aneurysms and one giant aneurysm. The contralateral pterional approach was used for two proximal-portion and one distal-portion aneurysms. Although most true PCoA aneurysms can be treated by the pterional approach, other means such as anterior temporal and subtemporal approaches can be applicable for aneurysms in the middle and distal portions of the PCoA or giant aneurysms. Surgeons should select an appropriate approach for each aneurysm while considering the advantages and disadvantages of each technique.
Keywords: true posterior communicating artery aneurysm; surgical approach; subtemporal approach; premammillary artery